The Role of the Government in Waste Management in Bahodopi District - Yunus; Irawati; Sisrilnardi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
In Bahodopi District, rapid population growth and expanding industrial activities have led to a significant accumulation of waste, revealing shortcomings in infrastructure and public awareness despite the existence of regulations. This study aims to examine how the local government addresses waste management by applying two conceptual frameworks, namely the dynamic aspect and the regulatory aspect, along with the facilitator concept by Ryas Rasyid. Using a qualitative method with a descriptive approach, data were collected through interviews and observations involving officials from the Morowali District Government, the Bahodopi Sub-District Government, the village governments of Keurea and Labota, as well as members of the local community, supported by relevant reports and documents. The findings indicate that government actions are often reactive, occurring only during emergencies or periods of increased public attention, while Regional Regulation No. 5 of 2017 has not been implemented effectively. Major obstacles include inadequate waste management facilities, limited transport fleets, and low public awareness. This study is expected to contribute to the literature on waste governance by local governments in mining areas such as Morowali District.